Into the Unknown: Uncertainty and Procrastination in Students From a Life History Perspective - Lim, Amy J.; Javadpour, Sasha (Frontiers in Psychology, 2021)
While existing findings have established an increase in procrastination among students in higher education during COVID-19, they do not elucidate how COVID-19 have effected an increase in procrastination. Drawing upon previous findings and employing a life history framework, this paper proposed that the increase in procrastination may be attributed to the heightened levels of uncertainty in the pandemic. Additionally, this paper examined life history strategy as the psychological mechanism underlying the relation between uncertainty and procrastination. By collecting data across two school semesters in a university (N = 253), we found that uncertainty and procrastination did not differ between the semester where changes were abruptly imposed to stem the spread of COVID-19 and the following semester. Our findings also revealed that uncertainty predicted procrastination, and that life history strategy mediated the relation between uncertainty and procrastination. Specifically, uncertainty was associated with a faster life history strategy, which was positively associated with procrastination. By shedding light on the psychology behind the effect of uncertainty on procrastination, the findings of this paper hold important implications for the design of procrastination interventions for the uncertain climate during the pandemic and “the new normal” post COVID-19.